PERAN KONSELOR DALAM PENANAMAN PENDIDIKAN ANTIKORUPSI BAGI SISWA SMPN 5 KEPANJEN - Fairus Abdi S (Jurnal Konseling Pendidikan Islam, 2020)
Abstract: Corruption comes from the Latin "corruputio" or "corruptus" meaning damage or corruption (Samidan, 2011). Meaning of the word corruption is corruption, literally, malice, depravity, dishonesty, can be bribed, immoral, deviations from the Holiness (Karsona, 2013). Corruption may be defined as a misappropriation or misuse of State money and private for personal benefit or others. The Act of corruption can also damage a country in terms of economy and education. Corruption in Indonesia is already very worrying, and needs to be eradicated altogether, during the handling of the corruption eradication more done in the form of repressive actions, namely the Act provides punishment by holding the corruptor. Other strategies in the fight against corruption, one of them with preventive action or prevention of the occurrence of corruption, this action which is considered the most effective way to prevent the occurrence of corruption, namely through education pathways. This type of research is a case study, Bungin (2003) describes research case study is a study that is comprehensive, intensive, detailed and insightful as well as more directed in an effort to elucidate the issues or phenomena the contemporary nature and immediacy. Anti-corruption education modules can be delivered through the role of the Counselor/teacher BK through granting information services by delivering anti-corruption education values for students of JUNIOR HIGH SCHOOL. Anti-corruption education could be developed back-related media provided against the students. Keywords: Anti-corruption Education, Counselors, Students